Productive Waqf Management and Socio Entrepreneurship: The Role of Mosque Based Family Waqf in Indonesia - Dikuraisyin, Basar; Yani, Achmad (Journal of Finance and Islamic Banking, 2025)
Purpose: This study examines a new model of family waqf asset management involving nadzir and wakif as socio-preneurs at the Sabilillah Mosque in Malang Indonesia. Until now, the problem of potential waqf land has been unable to be developed productively. Expert waqf land is also not managed due to traditional reasons. Method: This study offers a solution by using a qualitative case study approach, with data collected through in-depth interviews and document analysis involving mosque administrators (nazhir), wakif families, and beneficiaries. Results: The findings show that the family waqf management model by the nadzir effectively combines religious motivation with the principles of social entrepreneurship—emphasizing trusst, collaboration, and the creation of shared value rather than profit maximization. Implications: These research findings provide a new concept for managing productive waqf for the family micro-sector, particularly utilizing family land waqf to be productive through cooperation between the nadzir and wakif. Originality: This study identifies a new conceptual framework in which family waqf also benefits from waqf management to achieve family economic resilience. This model increases family income, strengthens social solidarity, and positions mosques as catalysts for social economy rather than merely religious institutions.